Obstructive Hemivagina with Ipsilateral Renal Agenesis in a 16-year-old Diabetic African Girl: a case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2025)
Background: The obstructed hemivagina with ipsilateral renal agenesis (OHVIRA) syndrome is a type of Müllerian duct anomaly (MDA) resulting from abnormal development of Müllerian ducts. Its features typically become apparent at puberty when girls present with menstrual abnormalities. The varied presentation of MDAs presents diagnostic and management challenges. Case presentation: A 16-year-old diabetic African girl presented to Savannah Healthcare with cyclical lower abdominal pain and foul-smelling per vagina discharge. Magnetic resonance imaging (MRI) showed complete duplication of the uterus, cervix, and vagina (uterine didelphys) with an obstructed left hemivagina with hematocolpos. The septum obstructing the hemivagina was resected with drainage of the hematocolpos. A follow-up abdominal renal ultrasound showed the absence of the left kidney. Conclusion: Careful clinical examination and MRI are essential for diagnosing OHVIRA syndrome. Prompt surgical intervention improves outcomes.